Epigenetic control by histone methylation - Jenuwein, Thomas (Henry Stewart Talks, 2007)
The diversity of covalent histone tail modifications for imparting epigenetic information, observations of robust histone modifications at silent chromatin regions, the representation of repressive histone marks as indications of epigenetic plasticity in different cells, analysis of the profiles of normal and aberrant histone lysine methylation patterns, as they occur during the transition of an embryonic to a differentiated cell or in controlled self-renewal vs. pro-neoplastic or metastatic conditions, elucidation of these histone modification patterns for novel advances in stem cell research, nuclear reprogramming and cancer
Reviewed at 2022/04/12